Koping Spiritualitas Kelurga dalam Perawatan Pasien yang Menjalani Hemodialisa - Ni Wayan Udayani; Nurhayati (PrimA: Jurnal Ilmiah Ilmu Kesehatan, 2023)
Background: The impact caused by hemodialysis will be felt by the family so that there is a need for a coping mechanism from the patient's family so that treatment for the patient can be optimal. The purpose of this study was to describe coping spirituality in the care of patients undergoing hemodialysis. Research Methods: This research is a descriptive qualitative research with a phenomenological approach. Data was collected by means of in-depth interviews, research instruments using interview guides and recording devices. The participants were 10 people, namely families of hemodialysis patients, hemodialysis patients, neighbors of hemodialysis patients and holders of the Prolanis program at Tabanan III Health Center. The data obtained were analyzed using the Colaizzi approach. Results: This study found 4 themes, 1.deep sadness, 2.family support in care, 3.spiritual approach helps to achieve peace, 4.hope for recovery. Conclusion: Participants in this study became an encouragement and support for all types of needs of family members undergoing hemodialysis in their care. The support given is in the form of spiritual to achieve peace in living life. Suggestion: Patients undergoing hemodialysis therapy always receive support from the family so that they do not experience deep sadness by taking a spiritual approach to achieve calm, by always being grateful and close to God even in health or illness by increasing spirituality as a form of gratitude to God.